2024
DOI: 10.2147/jir.s462722
|View full text |Cite
|
Sign up to set email alerts
|

Zooming in and Out of Programmed Cell Death in Osteoarthritis: A Scientometric and Visualized Analysis

Siyang Cao,
Yihao Wei,
Yaohang Yue
et al.

Abstract: During the past decade, mounting evidence has increasingly linked programmed cell death (PCD) to the progression and development of osteoarthritis (OA). There is a significant need for a thorough scientometric analysis that recapitulates the relationship between PCD and OA. This study aimed to collect articles and reviews focusing on PCD in OA, extracting data from January 1st, 2013, to October 31st, 2023, using the Web of Science. Various tools, including VOSviewer, CiteSpace, Pajek, Scimago Graphica, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…In contrast to prior inquiries, which primarily leaned on meta-analyses or narrative reviews, the employment of bibliometric tools in this research offered a more transparent depiction of research emphases and trajectories across diverse dimensions ( 29 , 31 , 33 , 90 , 91 ). This study marks the inaugural effort in the last decade to perform bibliometric analysis for delineating and delineating “BCS for breast cancer” knowledge landscapes, furnishing a thorough and impartial benchmark for forthcoming progressions, notwithstanding the presence of certain unavoidable constraints.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to prior inquiries, which primarily leaned on meta-analyses or narrative reviews, the employment of bibliometric tools in this research offered a more transparent depiction of research emphases and trajectories across diverse dimensions ( 29 , 31 , 33 , 90 , 91 ). This study marks the inaugural effort in the last decade to perform bibliometric analysis for delineating and delineating “BCS for breast cancer” knowledge landscapes, furnishing a thorough and impartial benchmark for forthcoming progressions, notwithstanding the presence of certain unavoidable constraints.…”
Section: Resultsmentioning
confidence: 99%
“…The method of retrieving and collecting data is illustrated in Figure 1A . The research progress of a study can be indicated by the quantity of scientific reports it produces within a specified period ( 26 29 ). From 2013 to 2023, a cumulative total of 5,586 pertinent scientific reports focusing on “BCS for breast cancer” were assembled.…”
Section: Resultsmentioning
confidence: 99%